Peran Sistem Pendukung Keputusan dalam Meningkatkan Efektivitas Pengambilan Keputusan - Indah Basma Sari; Devi Sintya Sari (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2025)
This study examines the role of Decision Support Systems (DSS) in improving the effectiveness of decision-making in educational institutions as complex organizations involving multiple stakeholders. The research aims to analyze in depth how DSS, through methods such as AHP and TOPSIS, provides structured data and objective analysis, thereby reducing subjectivity and supporting fast, accurate, and inclusive decision-making in line with democratic principles. Another objective is to identify forms of DSS integration in educational management that is adaptive and evidence-based, particularly in accelerating information processing, increasing managerial efficiency, and strengthening the quality of educational services.Using a library research method and descriptive analysis of recent literature, the study finds that the implementation of DSS accelerates information processing, minimizes decision errors, and enhances managerial efficiency and service quality through adaptive and evidence-based leadership. The integration of DSS supports decision-making processes that are transparent, participatory, and responsive to environmental changes, thereby strengthening the achievement of organizational goals. The practical benefits of this research are to provide theoretical and practical foundations for educational leaders in designing and implementing DSS as a transparent and participatory decision-making tool, as well as to serve as a reference for system developers, researchers, and education practitioners in optimizing the use of DSS technology to deal with complexity and uncertainty in educational management